2023
DOI: 10.3390/buildings13092290
|View full text |Cite
|
Sign up to set email alerts
|

Physicomechanical Behavior of High-Performance Concrete Reinforced with Recycled Steel Fibers from Twisted Cables in the Brittle State—Experimentation and Statistics

Yazid Chetbani,
Rebih Zaitri,
Bassam A. Tayeh
et al.

Abstract: This research studied the effect of recycled steel fibers extracted from twisted cable waste on the fresh and hardened states of high-performance concretes. Accordingly, slump, water absorption (WA), compressive strength (CS), flexural strength (FS), and split tensile strength (STS) were measured in the laboratory using mixtures generated by the response surface methodology (RSM). The RSM-based central composite design (CCD) was used to assess the influence of water-to-binder (W/B) ratios from 0.27 to 0.31, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Two-factor analysis of variance (ANOVA) with replications was employed to investigate the effects of two independent variables on the observed outcomes. Particle size, temperature, and pressure were manipulated as independent variables to evaluate both their individual impacts and potential interactions [32,33]. An ANOVA was performed on the dataset, which comprised a total of 102 data points.…”
Section: Discussionmentioning
confidence: 99%
“…Two-factor analysis of variance (ANOVA) with replications was employed to investigate the effects of two independent variables on the observed outcomes. Particle size, temperature, and pressure were manipulated as independent variables to evaluate both their individual impacts and potential interactions [32,33]. An ANOVA was performed on the dataset, which comprised a total of 102 data points.…”
Section: Discussionmentioning
confidence: 99%
“…When the R 2 value approaches 1, the accuracy of the proposed model increases illustrate that an increase in the Timchemt percentage, along with a reduction in the glass powder content from 5% to 0%, leads to high density values of up to 1.44 g/cm³ [12]. Figures 11 and 6 present 2D contour diagrams and 3D graphs to assess compressive strength and flexural strength at 28 days.…”
Section: Model Development and Anovamentioning
confidence: 98%
“…[3] Utilizing recycled fibers is a great way to lessen the impact on the environment and the amount of garbage that ends up in landfills. Numerous studies have demonstrated the economic viability and feasibility of using various fiber types recovered from waste sources in the manufacturing of reinforced concrete [5,8,12]. High carbon steel strands and wires make up wire ropes, which can deteriorate due to a number of factors, including fatigue-induced inter-wire friction and corrosion [9,17].…”
Section: Introductionmentioning
confidence: 99%